Dinamic Simulation Solidworks pada Perancangan Mesin Brush Sander - Uriansyah, Faridz Ashar; Rhohman, Fatkur (Jurnal Rekayasa Mesin, 2024)
This research aims to analyze the strength and response of the frame of the brush sunder machine to forces and loads. The research method involves using the SolidWorks application with an angle iron frame and ASTM 36 material. The research results include critical data such as stress, displacement, and safety factor. Applying forces and loads to the frame through the SolidWorks model allows for a thorough evaluation of the structural strength and its response. Stress data provides an overview of the maximum load, displacement identifies deformation, and the safety factor indicates the structural reliability level. This study is expected to contribute to a deeper understanding of the performance and safety of the brush sunder machine frame under various operational conditions.